2021
DOI: 10.18805/ijare.a-5768
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potassium and Iron Levels on Growth and Yield of Kharif Rice Bean (Vigna umbellata L.)

Abstract: Background: Rice bean (Vigna umbellata L.) has recently been notified as a promising pulse crop. It is grown for green manure, green fodder and pulses. Potassium plays a major role in increasing the legume yield and yield components, besides provides tolerance to stress such as high-low temperature and drought. Similarly, iron is important for chlorophyll synthesis and is a key component of the nitrogenase enzyme, which is important for nitrogen fixation.Methods: A field experiment was conducted during kharif … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The maximum average number of branches, plant height, and the number of leaves were found from plots receiving 20:20:20, 20:0:30, and 10:20:15 kg NPK/ha, and the corresponding minimum values were found from plots treated with 10:20:15, 0:0:0, and 20:0:30 kg NPK/ha. Although average values of the parameters were found to be different among treatments, statistically, these values were not significantly different, i.e., these values are at par with each other, which might be due to previous field conditions, extraneous soil factors, soil fertility gradient, soil moisture content, soil heterogeneity, soil texture, environmental factor, etc Swathi et al (2021). reported that the application of 20 kg K/ ha plus 15 kg Fe/ha produces an optimum level of plant parameters encompassing plant height, nodules per plant, plant dry weight, branches per plant, pods per plant, and seeds per pod.During an investigation on rice beans,Susilowati et al (2016) reported that the combination of 5 Mg organic fertilizer, 50% of recommended fertilizer, plus MVA induces the productivity and quality of the rice bean crop.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…The maximum average number of branches, plant height, and the number of leaves were found from plots receiving 20:20:20, 20:0:30, and 10:20:15 kg NPK/ha, and the corresponding minimum values were found from plots treated with 10:20:15, 0:0:0, and 20:0:30 kg NPK/ha. Although average values of the parameters were found to be different among treatments, statistically, these values were not significantly different, i.e., these values are at par with each other, which might be due to previous field conditions, extraneous soil factors, soil fertility gradient, soil moisture content, soil heterogeneity, soil texture, environmental factor, etc Swathi et al (2021). reported that the application of 20 kg K/ ha plus 15 kg Fe/ha produces an optimum level of plant parameters encompassing plant height, nodules per plant, plant dry weight, branches per plant, pods per plant, and seeds per pod.During an investigation on rice beans,Susilowati et al (2016) reported that the combination of 5 Mg organic fertilizer, 50% of recommended fertilizer, plus MVA induces the productivity and quality of the rice bean crop.…”
mentioning
confidence: 71%
“…It can be upright, semi-erect, or interweaving, while it does not always require support. It is usually 30-100 cm tall but can grow to be 200 cm tall (Swathi et al, 2021). It has a massive root hair with a tap root that may reach depths of 100 to 150 cm.…”
Section: Introductionmentioning
confidence: 99%